Nanotubes with well-defined structure: Single- and double-walled imogolites - Lourenco, Maicon P.; Guimaraes, Luciana; Da Silva, Mauricio Chagas; De Oliveira, Claudio; Heine, Thomas; Duarte, Helio A. (Journal of Physical Chemistry C, 2014)
We have investigated the structure and electronic structure of single- and double-walled imogolite nanotubes with Ge and Si as group IV element. While it is known from experiment, and in the case of single-walled tubes confirmed by theory, imogolite nanotubes are monodisperse in diameter. We show that imogolite tubes are also showing a preferred chirality (zigzag), resulting from the hydrogen-bond network on the tube surfaces, and that there is an exceptionally stable form of intertube interaction that supports the formation of monodisperse double-walled imogolite nanotubes. The strongest stabilization of double-walled tubes has been found for tube indexes with nine units of difference around the circumference, and the minimum structure is found for the (12,0)(21,0) tube in the case of germanium imogolite and (9,0)(18,0) for imogolite. The electronic structure is only slightly affected by these geometric factors, as are the mechanical properties, which show Young moduli of 320-370 GPa, thus being in the same range as other clay mineral nanotubes. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20